Outcomes of Perianal Fistulising Crohn's Disease Following Anti-TNFα Treatment Discontinuation. Issue 6 (4th May 2018) - Legué, Clémence; Brochard, Charlène; Bessi, Grégoire; Wallenhorst, Timothée; Dewitte, Marie; Siproudhis, Laurent; Bouguen, Guillaume
Abstract: Background: Discontinuation of antitumour necrosis factor (TNF)α therapy with perianal fistulising Crohn's disease remains controversial due to the risk of severe relapse without any clear evidence. Aim: The aim of this study was to assess the rate and type of perianal and luminal relapses following anti-TNFα discontinuation. Methods: All patients treated with anti-TNFα for perianal fistulising Crohn's disease with subsequent discontinuation of therapy were retrospectively reviewed from a prospective database (1998–2016). Cumulative probabilities of relapse-free survival were estimated by actuarial analysis. Results: After a median follow-up of 62 months, 24 of the 45 patients experienced perianal relapse. A new surgical drainage was needed in 19 (79%) patients. The cumulative probabilities of perianal relapse at 1 and 5 years were 24% and 55%, respectively. Ileal localization (L1) at diagnosis, persistence of an external fistula opening, second line anti-TNFα use, or prior dose optimization was associated with perianal relapse, whereas continuation of immunosuppressive agents decreased this risk (HR = 0.3). Luminal relapse occurred in 42% of patients at 5 years. The cumulative probability of global relapse at 5 years was 67%. Retreatment with anti-TNFα allowed further remission in 23 of 24 (96%) patients. Conclusion: Half of patients with perianal fistulising Crohn's disease relapse within 5 years after anti-TNFα discontinuation. Immunosuppressant continuation may decrease this risk. The high risk of relapse (perianal and luminal) may suggest a benefit in pursuing biologics over a longer period in patients with perianal fistulas.